The pH-induced physical properties of ionic contact lens material. Issue 2 (February 2023) - Ahn, Jihye; Choi, Moonsung
Abstract: The degree of protonation of contact lens materials is affected by the surrounding pH environment, due to the different pKa values. The swelling of ionic contact lenses is generally controlled by these factors which determines physical properties of contact lenses. The purpose of this study was to evaluate the pH dependence of the physical properties of contact lenses. The ionic etafilcon A and non-ionic hilafilcon B contact lenses were used in this study. The diameter, refractive power, equilibrium water content (EWC), and the amounts of freezable-free water (Wff ), freezable-bound water (Wfb ) and non-freezable water (Wnf ) in the contact lens at each pH condition were measured. The diameter, refractive power and EWC of etafilcon A decreased with decreasing pH below 7.0 or 7.4, whereas hilafilcon B showed relatively constant values. The quantity of Wfb tended to increase with increasing pH, showing a relatively constant value above 7.0, whereas Wnf decreased. Hilafilcon B did not show changes in EWC and specific trends in Wfb and Wnf . The significant change of etafilcon A at more acidic condition is derived from the presence of methacrylic acid (MA) which makes it vulnerable to pH. Additionally, though the EWC is composed of various states of water, (i) various states of water could response to surrounding environment in different way with EWC and (ii) Wfb could be the crucial factor that determines physical properties of contact lens.